2013
DOI: 10.1111/jpim.12100
|View full text |Cite
|
Sign up to set email alerts
|

What Keeps Managers Away from a Losing Course of Action? Go/Stop Decisions in New Product Development

Abstract: The purpose of this experimental study is to test whether specific approaches can reduce escalation of commitment—namely, decision‐makers' tendency to persist with an innovation project despite negative feedback that the initial investment has not reached its goals. This study focuses on the decision process for 137 research and development managers who must decide whether to abandon previously chosen courses of action or to continue in the face of probable and increasing losses in a stage‐gate system. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 59 publications
(133 reference statements)
1
28
0
Order By: Relevance
“…Transparent but tough decisions also allow for uncomfortable changes such as the termination of innovation projects (Behrens and Ernst, ). For example, Unger et al () show that firms making rigorous termination decisions achieve a better strategic fit of their portfolio, because they can more quickly reallocate resources and refocus the portfolio.…”
Section: Hypothesesmentioning
confidence: 99%
“…Transparent but tough decisions also allow for uncomfortable changes such as the termination of innovation projects (Behrens and Ernst, ). For example, Unger et al () show that firms making rigorous termination decisions achieve a better strategic fit of their portfolio, because they can more quickly reallocate resources and refocus the portfolio.…”
Section: Hypothesesmentioning
confidence: 99%
“…Two exceptions are Green et al (2003), who found that projects were less likely to be terminated when they enjoyed greater levels of management advocacy, and Shepherd et al (2014), whose study reveals the complex dynamics around project termination timing-showing both positive and negative consequence of delayed termination. Nevertheless, most studies on project termination have been experimental (e.g., Behrens and Ernst, 2014;Biyalogorsky et al, 2006;Boulding et al, 1997;Eliëns et al, 2018;McNally et al, 2013;Schmidt and Calantone, 1998). Using a unique data set on drug development, we aim to fill this void.…”
Section: Introductionmentioning
confidence: 99%
“…Even innovation projects that fare well are often terminated before they are completed because of strategic portfolio management considerations (Krishnan and Ulrich, 2001). Such terminations may be of managerial necessity in order to avoid unnecessary losses, to release resources from unpromising endeavors, or to align the innovation project portfolio with the overarching strategy (Behrens and Ernst, 2014;Krishnan and Ulrich, 2001). However, despite these beneficial aspects, terminating innovation projects can have strong and detrimental effects on the innovators involved (Shepherd, Haynie, and Patzelt, 2013;Shepherd, Patzelt, and Wolfe, 2011;V€ alikangas, Hoegl, and Gibbert, 2009).…”
Section: Introductionmentioning
confidence: 99%